THE ROLE OF PT BANK ACEH'S DIGITAL TRANSFORMATION IN SUPPORTING MSMEs DRIVING HALAL TOURISM IN ACEH PROVINCE - Aprullah, Muhammad Putra; Adria, Agus; Sayuthi, Muhammad; Fuadi, Raida; Julnadi, Salsabilla (Islamic Economics Program, Faculty of Islamic Economics and Business, 2024)
The research aims to discuss the role of Bank Aceh's digital transformation in developing halal tourism in Aceh Province. The concept of tourism development that remains in synergy with the cultural values of the Acehnese people who are thick with Islamic values. The people of Aceh have a strong commitment to implementing Islamic law in a kaffah manner and in all activities of life. Bank Aceh's digital transformation is very important to support the development of halal tourism in Aceh Province. Bank Aceh must consider three main factors in carrying out digital transformation as a means of supporting the development of halal tourism. First, halal tourism is developed based on the values of Islamic law, national law and qanun (regional regulations). Second, the importance of halal certification in all types of services. Third, the active involvement of PT Bank Aceh in the feasibility study of capital and MSMEs assistance in managing tourist attractions, tourism marketing, tourism industry, and institutional development. These three factors need to be fully supported by integrative government and financial industry policies. This research is expected to contribute to the development of knowledge about the role of digital transformation of PT Bank Aceh in developing halal tourism in Aceh Province.